AI Cyberspace war between Pakistan and India; its impact on USA Policies towards south Asia Region - Zainab Iftikhar (Social Science Review Archives, 2025)
The purpose of this study is to investigate how Ai driven cyberspace between Pakistan and India has grown to be its significant aspect of their geopolitical competition, significantly influencing the stability and security of the area. This study primarily aims to focus on the effects of the cybersecurity between two nations which have previously been made worse by political disputes and terrorism attacks, territorial disputes and military conflict. Both countries have added cyber capabilities in strategic arsenals since this new kind of warfare has a number of unique and varied threats, including the damage of vital infrastructure, financial losses, and psychological effects on civilian population. The majority of these cyber-attacks are included in a study which is more globally significant in terms of the south Asia region. This article employed a Qualitative form of methodology. This cyberwarfare affects the USA foreign, economic, defensive, strategic, geopolitical policies regarding south Asia region. USA wants to dominance in the south Asia region and for this purpose USA make ties with India Because US see India investing more technology advancement and AI militarization to Compete with China and USA also wants to counter china in south Asia region. Despite these factors USA also make Balancing policies between India and Pakistan for the sake of regional stability and its dominance the area.